Duri dalam Sekam - Johan Wahyudi; Lesi Maryani; M Dien Madjid (INC- Islam Nusantara Center, 2022)
This article explores the resistance of the Bengkulu people to the Dutch East Indies government in the last XIX century to the beginning of the XX century. It is suspected that the colonial government's interest in building colonies in this country is to control and monopolize the trade of various spices such as pepper, cloves, nutmeg and so on. In addition, they are also interested in mastering the gold mine in Rejang Lebong. Searches of various Dutch archives such as the Koloniaal Verslag were carried out in order to obtain primary sources on this topic. The research method used is to raise the social history of the Bengkulu community, especially regarding the role of community elites such as regional heads, clerics, hajj who have an important contribution in moving the people. The novelty obtained is that information about the war in Bengkulu occurred communally and partially but was quite troublesome for the colonial position there. Artikel ini mengupas seputar perlawanan masyarakat Bengkulu terhadap pemerintah Hindia Belanda pada kahir abad XIX hingga awal abad XX. Ditengarai, ketertarikan pemerintah kolonial membangun koloni di negeri ini adalah guna menguasai dan memonopoli perdagangan aneka rempah-rempah seperti lada, cengkeh, pala dan lain sebagainya. Di samping itu, mereka juga tertarik meguasai tambang emas yang ada di Rejang Lebong. Penelusuran aneka arsip Belanda seperti Koloniaal Verslag dilakukan guna mendapat sumber primer mengenai topik ini. Metode penelitian yang digunakan adalah mengangkat sejarah sosial masyarakat Bengkulu, khususnya mengenai peran para elit masyarakat seperti kepala daerah, ulama, haji yang memiliki kontribusi penting dalam menggerakkan rakyat. Kebaruan yang diperoleh adalah informasi mengenai perang di Bengkulu terjadi secara komunal dan parsial namun cukup merepotkan kedudukan kolonial di sana.